Isotope Effects in the Predissociation of Excited States of N2+ Produced by Photoionization of 14N2 and 15N2 at Energies Between 24.2 and 25.6 eV - Hrodmarsson, Helgi R.; Thissen, Roland; Dowek, Danielle; Garcia, Gustavo A.; Nahon, Laurent; Govers, Thomas R. (Frontiers in Chemistry, 2019)
Photoelectron/photoion imaging spectrometry employing dispersed VUV radiation from the SOLEIL synchrotron has been used to study the predissociation of N2+ states located up to 1.3 eV above the ion's first dissociation limit. Branching ratios for unimolecular decay into either N2+ or N+ were obtained by measuring coincidences between threshold electrons and mass-selected product ions, using a supersonic beam of either 14N2 or 15N2 as photoionization target. The results confirm that predissociation of the C2Σu+ state of 14N2+ is faster than emission to the electronic ground-state by a factor 10 or more for all vibrational levels v′ ≥ 3, while for 15N2+ the two decay modes have comparable probabilities for the levels v′ = 3, 4, and 5. In contrast, no significant isotope effect could be observed for the other states of N2+ identified in the photoelectron spectrum. For both 14N2+ and 15N2+ isotopologues all vibrational levels of these other states decay to an extent of at least 95% by predissociation.